Coordination polymer of copper with a silicon-containing Schiff base: Synthesis, structural characterization, and properties. (August 2015) - Zaltariov, Mirela-Fernanda; Cazacu, Maria; Vlad, Angelica; Sacarescu, Liviu; Shova, Sergiu
A Schiff base was prepared by condensation reaction of 2, 6-diformyl-4-methylphenol with trimethylsilyl-methyl- p -aminobenzoate and it was further used, without isolation, as a ligand for copper (Cu(II)) ions. The structure of the resulting coordination complex was evidenced by spectral techniques (Fourier transform infrared spectroscopy, nuclear magnetic resonance and ultraviolet-visible spectroscopy) and by single crystal X-ray diffraction, which revealed a covalent one-dimensional (1D) structure where neutral molecular units (Cu(II) coordination polymer [CuL2 ]) are linked through the bridging oxygen atoms. The 1D polymeric chains are associated by intermolecular C–H···O hydrogen bonding to form two-dimensional supramolecular layers. The polymeric nature of the compound was also supported by the presence of glass transition in differential scanning calorimetry trace. This coordination polymer forms spherical aggregates in a nonpolar medium (hexane) as was emphasized by transmission electron microscopy image taken on the film remained after solvent evaporation. The thermogravimetrical analysis indicates a good stability for the Cu(II) coordination polymer and the biological tests revealed good antibacterial and antifungal activities.